Effect of low frequency magnetic field on cardiovascular system - Ali, Esmail A. M. (Journal of Scientific and Engineering Research, 2021)
The effect of exposing magnetic fields (MFs) with low frequency on human cardiovascular parameters are still unidentified. As a predictor of specific cardiovascular pathologies, estimating the exposure of employees workplace with dosimeters by changed variability of heart rates is performed in epidemiological studies. Besides, microcirculatory factors such as blood pressure, variability of heart rates or heart rates are concentrated on by laboratory studies. Studies about microcirculatory systems responses to exposing low frequencymagnetic fields are sparse. In the international existing re-evaluation contexts of exposure guidelines, tackling such issues is important for further studies regarding low frequencymagnetic fields, international exposure guideline re-evaluation. In these studies, the potential negative and positive influences of low frequencymagnetic fields and the detections and characterizations of their induced subtle physiological changes should be addressed. The investigation of the micro- and macro-circulatory relationships and the utalization of laboratory geomagnetic shielding are recommended for futher studies. The micro- and macro-circulation, lymph vascular system, and heart are included in the cardiovascular system. Although the cardiovascular systems mechanics and characteristics had a wide discussion in literature which is beyond this paper scope, a consise description of this system was conducted for the facilitatation of understanding the effects of exposing low frequency magnetic fields on human cardiovascular parameters.